TINJAUAN ATAS SISTEM INFORMASI AKUNTANSI PADA PEMBAYARAN UTANG USAHA PT.ELNUSA TBK - Oktri Johannes (2020)
The Final Project report aims to develop the abilty of student, find out how much application of the theory that has been given in lectures with the practice that has been implemented, and can measure their own quality in the world of work. This internship is conducted at Pt.Elnusa Tbkis located on Jl.T.B Simatupang Kav.1B,South Jakarta 12560. In carrying out the internship, there are many benefits, one of which is to improve and expand the capabilities possessed in the real world of work. And expanding the use of accounting information systems for the payment of trade payables in the world of work, strating from the collection of accounts payable. Conduct tax audits on trade payables until the trade payables are paid and paid off. So that in carrying out practical work in the review of business debt payment, it can be concluded that it can shape the mentality of student in the world of work. So that it can be used as capital for students in entering the real world of work and ini the masses to come.